Association between plasma lipoprotein levels and bioprosthetic valve structural degeneration. Issue 23 (4th July 2016) - Nsaibia, Mohamed Jalloul; Mahmut, Ablajan; Mahjoub, Haifa; Dahou, Abdellaziz; Bouchareb, Rihab; Boulanger, Marie-Chloé; Després, Jean-Pierre; Bossé, Yohan; Arsenault, Benoît J; Larose, Eric; Pibarot, Philippe; Mathieu, Patrick
Abstract : Introduction: Structural valve degeneration (SVD) leads to the failure of aortic valve bioprostheses. It is suspected that lipid-derived factors could play a role in SVD. We hypothesised that oxidised low-density lipoprotein (OxLDL), OxLDL/LDL, OxLDL/high-density lipoprotein (OxLDL/HDL) and proprotein convertase subtilisin/kexin 9 (PCSK9) may be associated with SVD. Methods: We included 199 patients who underwent an aortic valve replacement with a bioprosthesis and had an echocardiography follow-up to evaluate the function of the prosthesis. SVD was defined as an increase in mean transprosthetic gradient (≥10 mm Hg) or a worsening of transprosthetic regurgitation (≥1/3) during the follow-up. Results: After a mean follow-up of 8±3.5 years, 41(21%) patients developed SVD. The univariate predictors of SVD were LDL (p=0.03), apolipoprotein B (p=0.01), OxLDL (p=0.02), OxLDL/HDL (p=0.009) and LDL associated with small, dense particles (LDL-C<255Å ) (p=0.02). In a model adjusted for covariates, only OxLDL/HDL (OR 1.49, 95%CI 1.08 to 2.07 per 10 units, p=0.01) remained associated with SVD. There was a significant interaction between OxLDL/HDL and PCSK9 on SVD (p=0.05). After adjustment, compared with patients with low OxLDL/HDL (median, <25.4) and low PCSK9 (median, <298 ng/mL) (referent), patients with both an elevated OxLDL/HDL ratio and PCSK9 had a higher risk of SVD (OR 2.93, 95% CI 1.02 to 9.29, p=0.04). Conclusions: OxLDL/HDL ratio is independently associated with SVD.